Effects of interferon-?-2b and octreotide on healing of esophageal corrosive burns - Kaygusuz, I; Çelik, O; Özkaya, Ö; Yalçin, S; Keles, E; Çetinkaya, T (Wiley, 2001)
Objective. The aim of this study was to investigate the effect of interferon-alpha to 2b and octreotide on the treatment of esophagus corrosive burns. Method: The experimental study was performed on 63 rabbits. Burn was obtained by treating a segment, isolated in cervical esophagus, with NAOH. The rabbits were allocated into three groups (control, interferon, and octreotide). On the fourth, eighth, and 20th days, 7 rabbits randomly selected from each group were killed. Comparisons among the groups were made by taking histopathologic findings, stenosis index, and hydroxyproline production into consideration. Cross-tabulation and analysis of variance tests were used for statistical analysis. Results: There were no statistically significant differences among the groups in terms of epithelial changes, extension of inflammation, and severity of fibrosis. In terms of severity of inflammation, there was a statistically Significant difference between the control and the other two groups. Also, a significant difference was found between the control group and the other two groups in terms of extension of fibrosis on the 20th day. The difference between the control and the two treatment groups was significant on the eighth day and the 20th day measurements. Comparison of the hydroxyproline values showed a statistically significant difference between the octreotide group and the other two groups on the eighth and 20th days. Conclusion: Histopathologic and biochemical findings indicate that, by hindering fibrosis progress, octreotide (and interferon) might be new and promising alternatives in the treatment of corrosive burns of the esophagus.
Keywords: esophagus; corrosive burn; octreotide; interferon-alpha-2b